Herschel, Spitzer and Magellan infrared observations of the star-forming region RCW 121 (IRAS 17149−3916) - Tapia, M. (2014)
We present new deep near-infrared broad- and narrow-band imaging and low-resolution spec-troscopy of the star formation region RCW 121 (IRAS 17149−3916) which we analyse incombination withHerschel(70, 160, 250, 350 and 500μm) andSpitzer(3.6, 4.5, 5.8 and 8μm)images. The near-infrared photometry reveals the presence of a stellar cluster of approximatesize of 92 arcsec which is composed of at least 264 members, approximately 25 per cent ofthese showing excess emission atλ>2.0μm, indicative of circumstellar discs. Isochronescorresponding to ages 0.5–1.0 Myr andAV=7.8 fit well the position of a large fraction of likelycluster members in theKsversusH−Ksdiagram. We find three massive star-forming coreslocated in the boundaries of an expanding HIIregion ionized by a central O-type star. Fromtheir far-infrared spectral energy distributions (SEDs) we derive masses and temperatures ofthe dense cores. When these young stellar objects (YSOs) have warm emission components,the 1.2–500μm SEDs are fitted with Robitaille et al.’s star–disc-envelope model to obtain theirphysical parameters. The masses of the three YSOs are between 8 and 10 M . The youngestsite (core I) is undetected atλ<100μm and is at the earliest evolutionary stage that cancurrently be detected. The other two cores (II and III) contain YSOs of similar masses andhave near-infrared counterparts, which imply a more advanced evolutionary stage. The YSOat core II has been found to have associated a jet, with strong H2line emission, co-existingwith an H2O maser source. RCW 121 is another example of multiple star formation beingtriggered by the expansion of a single HIIregion.